2020
DOI: 10.21203/rs.3.rs-19662/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of In Vitro resistance to fluoroquinolones in Pseudomonas aeruginosa

Abstract: Background: The objectives of this study were to investigate the dynamics of different resistant mechanisms in P.aeruginosa populations that have evolved under fluoroquinolone pressure, and any interactions between these mechanisms in the evolutionary trajectories. Methods:In this study, bacteria of the strain ATCC27853 were selected under different concentrations of levofloxacin and ciprofloxacin for six parallel lineages. The four target genes in the quinolone-resistance determining region were amplified and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…P. aeruginosa 6294, 6206, Paer1, ATCC 19660 were screened for their ability to develop resistance against AMPs and ciprofloxacin at sub-MIC (one-fold below the MIC), but did not develop resistance (data not shown). P. aeruginosa ATCC 27853 has previously been used to examine its susceptibility to a variety of antimicrobial agents [ 47 , 48 , 49 , 50 ], shown to be heteroresistant to colistin [ 51 ], and used to examine the ability of P. aeruginosa to develop resistance to a variety of antimicrobial agents [ 52 , 53 , 54 ]. This strain’s ability to develop resistance against AMPs and ciprofloxacin at sub-MICs (one-fold below the MIC) was examined as previously described [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…P. aeruginosa 6294, 6206, Paer1, ATCC 19660 were screened for their ability to develop resistance against AMPs and ciprofloxacin at sub-MIC (one-fold below the MIC), but did not develop resistance (data not shown). P. aeruginosa ATCC 27853 has previously been used to examine its susceptibility to a variety of antimicrobial agents [ 47 , 48 , 49 , 50 ], shown to be heteroresistant to colistin [ 51 ], and used to examine the ability of P. aeruginosa to develop resistance to a variety of antimicrobial agents [ 52 , 53 , 54 ]. This strain’s ability to develop resistance against AMPs and ciprofloxacin at sub-MICs (one-fold below the MIC) was examined as previously described [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Measures to reduce the occurrence of drug-resistant strains must also be addressed even though treatment compliance is critical to clinical outcomes. More importantly, IDentif.AI-designed combinations all contained LVX, a fluoroquinolone antibiotic that is highly prone to induce drug resistance 59 - 61 . IDentif.AI pinpointed interactions (LVX/MEM and LVX/RFB) both contained LVX and only exhibited mild interactions, which may lead to drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted for the identification of mutations in the QRDR regions, of which the missense mutation is the most prevalent mutation. The study conducted by Zhao et al (2020) has observed that the mutations occurred in clinical isolates with the presence of ciprofloxacin and levofloxacin pressure. Ciprofloxacin pressure showed 3 major mutations occurred in gyrA, (gyrA83 and gyrA87), whereas the varying amino acid substitution was observed in the presence of levofloxacin pressure (gyrA83, gyrB466, parE457) (Zhao et al, 2020).…”
Section: Mutation In Fluoroquinolones Resistancementioning
confidence: 99%
“…The study conducted by Zhao et al (2020) has observed that the mutations occurred in clinical isolates with the presence of ciprofloxacin and levofloxacin pressure. Ciprofloxacin pressure showed 3 major mutations occurred in gyrA, (gyrA83 and gyrA87), whereas the varying amino acid substitution was observed in the presence of levofloxacin pressure (gyrA83, gyrB466, parE457) (Zhao et al, 2020). The results of the other study also showed a similar finding along with the parC mutation (Nouri et al, 2016) and in addition to that, the other 3 mutations occurred at 88, 104 and 121 sites in gyrA; no mutation was seen in gyrB, parE (Khademi et al, 2021).…”
Section: Mutation In Fluoroquinolones Resistancementioning
confidence: 99%